(3eHGOF GdJfXje hGdGOGQI (B/s - (3GdUjQaj, eMeOYHO GdaJGMs ((3YeGf(B: s (3OGQ GdefGgL(B, s, 2006)
(3CJj gPG GdcJGH GdPj jbUO Hg EKGQI GgJeGe GdbGQF HGdeHGOF hGdCSS GdEOGQjI(B. (3hGdcJGH dG jCJj HLOjO aj GdCUhd hGdeHGOF GdYdejI, hdcfg LOjO cd GdLqOI aj CSdhH GdYQV GdTGFb hGdLPGH hGdPj bUO efg EKGQI GgJeGe GdbGQF Gdi LGfH Pdc abO cGf dOi GdeDda CgOGa KdGKI JMceJ aj YQVg deNJda ehVhYGJ cJGHg GdJj cGfJ cGdJGdj GdebOeI(B-(3GdaUd GdChd (B: (3eGgjI GdEOGQI (B: (3eaghe GdEOGQI (B: (3NUGFU GdEOGQI (B: (3CgejI GdEOGQI (B: (3CgOGa GdEOGQI (B: (3GdegGQGJ GdEOGQjI (B: (3GdeHGOF GdEOGQjI (B: (3GdEOGQI Hjf Gdaf hGdYde (B: (3egfjI GdEOGQI (B: (3eSDhdjGJ GdEOGQI (B: (3GdHjFI GdEOGQjI(B-(3GdaUd GdKGfj (B: (3GdfXQjGJ GdEOGQjI (B: (3eaghe GdfXQjI (B: (3CgejI GdfXQjI GdEOGQjI (B: (3eYGjjQ GdfXQjI (B: (3eUGOQ HfGA GdfXQjI GdEOGQjI (B: (3eYhbGJ bHhd GdfXQjI GdEOGQjI (B: (3fXQjGJ GdEOGQI (B: (3GdfXQjGJ GdEOGQjI GdMOjKI(B-(3GdaUd GdKGdK (B: (3GdJNWjW (B: (3eaghe GdJNWjW (B: (3eHGOF GdJNWjW (B: (3CgejI GdJNWjW (B: (3GdYhGed GdeDKQI Ydi GdJNWjW (B: (3CHYGO GdJNWjW (B: (3eOGNd GdJNWjW (B-(3GdaUd GdQGHY (B: (3GdJfXje (B: (3eaghe GdJfXje (B: (3eHGOF GdJfXje(B- (3GdaUd GdNGeS (B: (3GdJhLjg GdEHOGYj (B: (3eHGOF GdJhLjg (B: (3CgejI GdJhLjg (B: (3TQhW fLGM GdJhLjg (B: (3NWhGJ GdJhLjg(B-(3GdaUd GdSGOS (B: (3GdQbGHI GdEHOGYjI (B: (3eaghe GdQbGHI (B: (3CgOGa GdfXGe GdQbGHj (B: (3NUGFU GdQbGHI (B: (3GdYedjI GdQbGHjI(B.s
(3HjHdjhZQGajG U(B. 323s
Keywords: (3GOGQIs; (3GOGQI GYeGds